Assembly of Fillable Microrobotic Systems by Microfluidic Loading with Dip Sealing. Issue 13 (26th February 2023) - Sun, Rujie; Song, Xin; Zhou, Kun; Zuo, Yuyang; Wang, Richard; Rifaie‐Graham, Omar; Peeler, David J.; Xie, Ruoxiao; Leng, Yixuan; Geng, Hongya; Brachi, Giulia; Ma, Yun; et al.
Abstract: Microrobots can provide spatiotemporally well‐controlled cargo delivery that can improve therapeutic efficiency compared to conventional drug delivery strategies. Robust microfabrication methods to expand the variety of materials or cargoes that can be incorporated into microrobots can greatly broaden the scope of their functions. However, current surface coating or direct blending techniques used for cargo loading result in inefficient loading and poor cargo protection during transportation, which leads to cargo waste, degradation and non‐specific release. Herein, a versatile platform to fabricate fillable microrobots using microfluidic loading and dip sealing (MLDS) is presented. MLDS enables the encapsulation of different types of cargoes within hollow microrobots and protection of cargo integrity. The technique is supported by high‐resolution 3D printing with an integrated microfluidic loading system, which realizes a highly precise loading process and improves cargo loading capacity. A corresponding dip sealing strategy is developed to encase and protect the loaded cargo whilst maintaining the geometric and structural integrity of the loaded microrobots. This dip sealing technique is suitable for different materials, including thermal and light‐responsive materials. The MLDS platform provides new opportunities for microrobotic systems in targeted drug delivery, environmental sensing, and chemically powered micromotor applications. Abstract : An integrated technique to fabricate fillable microrobotic systems is developed based on microfluidic loading with dip sealing (MLDS). The fillable chamber design isolates the loaded cargo from its surroundings, maintains cargo stability, and facilitates high loading capacity. This technique expands opportunities in microrobotics for targeted on‐demand cargo release and biosensing with an all‐in‐one fabrication method.